Mengembangkan Nilai-Nilai Karakter Siswa Melalui Pembelajaran IPS di Sekolah Dasar - Azizah, Septina Noor; Ismaya, Erik Aditia (Peneliti.net, 2024)
The character values of the younger generation, especially elementary school students, have been eroded by the growing current of globalization. This research aims to instill character values through social studies learning so that students can become individuals who better reflect the nation’s children and improve their character values. The library research method was used in this research, by collecting data from library materials and using documentation techniques. Researchers collected data from articles and ebook contained in online journal. The research result show that social studies learning can include character values through the elements instilled in students. Therefore, educators need to be able to instill character values well in social studies learning in elementary schools.